Outcome after associating liver partition and portal vein ligation for staged hepatectomy and conventional two‐stage hepatectomy for colorectal liver metastases. Issue 11 (12th August 2016) - Adam, R.; Imai, K.; Castro Benitez, C.; Allard, M.‐A.; Vibert, E.; Sa Cunha, A.; Cherqui, D.; Baba, H.; Castaing, D.
Abstract : Background: Although associating liver partition and portal vein ligation for staged hepatectomy (ALPPS) has been increasingly adopted by many centres, the oncological outcome for colorectal liver metastases compared with that after two‐stage hepatectomy is still unknown. Methods: Between January 2010 and June 2014, all consecutive patients who underwent either ALPPS or two‐stage hepatectomy for colorectal liver metastases in a single institution were included in the study. Morbidity, mortality, disease recurrence and survival were compared. Results: The two groups were comparable in terms of clinicopathological characteristics. ALPPS was completed in all 17 patients, whereas the second‐stage hepatectomy could not be completed in 15 of 41 patients. Ninety‐day mortality rates for ALPPS and two‐stage resection were 0 per cent (0 of 17) versus 5 per cent (2 of 41) ( P = 0·891). Major complication rates (Clavien grade at least III) were 41 per cent (7 of 17) and 39 per cent (16 of 41) respectively ( P = 0·999). Overall survival was significantly lower after ALPPS than after two‐stage hepatectomy: 2‐year survival 42 versus 77 per cent respectively ( P = 0·006). Recurrent disease was more often seen in the liver in the ALPPS group. Salvage surgery was less often performed after ALPPS (2 of 8 patients) than after two‐stage hepatectomy (10 of 17). Conclusion: Although major complication and 90‐day mortality rates of ALPPS were similar to those of two‐stage hepatectomy, overall survival was significantly lower following ALPPS. Abstract : Overall survival worse after ALPPS